The relationship of the pronunciation to the inflectional movements In the Holy Quran and its significance (Journal of the College of Basic Education, 2022)
The relationship between the Arabic language is a strong relationship that began from the beginning of its descent and the thinking of its meaning and the eloquence of the word in it. As we know that the methods of composition in the Holy Quran are very precise and have goals in all its details, the Holy Quran came with new words, meaning, purpose and style. When it comes down to the splendor, eloquence and smoothness of the word and meaning. The Qur'an has become a source of controversy among scholars in the Arabic language and between skeptics and those who are notoriously ignorant of the lack of rhetoric and intent in the Quranic pronunciation and composition. This research is intended to reinforce what scholars and researchers have previously stated in the consolidation and validation of the Qur'anic grammar and the extent of its communication